The effect of welding current on the mechanical properties of ST60 steel in the SMAW welding process - Tuafiq; Fahrul Rozi; Abubakar (Journal of Mechanical Engineering and Fabrication, 2024)
Welding current greatly affects the strength of the material connection so that a study is needed considering the many uses of welding processes in industrial construction. This study aims to determine the effect of welding current on mechanical properties using the SMAW welding process with current variations of 100 A, 110 A and 120 A. The material used is ST60 steel with a thickness of 10 mm, a single V butt joint type with an angle of 70 °. From the results of tests that have been carried out on test specimens using current variations, data is obtained that the average stress value of each current variation is, current 100A = 25.49 Kgf / mm², current 110A = 27.23 Kgf / mm² and current 120A = 26.49 Kgf / mm². The average strain value of each current variation is, current 100A = 1.5%, current 110A = 2% and current 120A = 2.16%. The average elastic modulus value of each current variation is, current 100A = 16,360 N/mm², current 110A = 12,554 N/mm² and current 120A = 11,947 N/mm². Based on these data, the optimal current is 120A.